2020
DOI: 10.21203/rs.3.rs-96288/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of the Bacterial Microbiome of Rhipicephalus (Boophilus) Microplus Collected From Pecari Tajacu “sajino” Madre De Dios, Peru

Abstract: Background: Ticks are arthropods that can host and transmit pathogens to wild animals, domestic animals, and even humans. Methods: The bacterial microbiome of adult (males and females) and nymph Rhipicephalus microplus ticks collected from a collared peccary, Pecari tajacu, captured in the rural area of ​​Botijón Village in the Amazon region of Madre de Dios, Peru, was evaluated using metagenomics. Results: The Chao1 and Shannon–Weaver analyses indicated greater bacterial richness and diversity in female ticks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
1
0
1
Order By: Relevance
“…Las garrapatas colectadas de T. pecari y P. tajacu fueron clasificadas como A. naponense y las colectadas de C. denticulata como A. humerale. Estudios previos han demostrado la distribución especies del género Amblyomma en animales silvestres como en Tapirus terrestres y C. denticulata de la selva de Madre de Dios en Perú (Del Valle et al, 2018;Esser et al,2016;Rojas-Jaimes et al, 2021). Figura 3.…”
Section: Resultados Y Discusiónunclassified
“…Las garrapatas colectadas de T. pecari y P. tajacu fueron clasificadas como A. naponense y las colectadas de C. denticulata como A. humerale. Estudios previos han demostrado la distribución especies del género Amblyomma en animales silvestres como en Tapirus terrestres y C. denticulata de la selva de Madre de Dios en Perú (Del Valle et al, 2018;Esser et al,2016;Rojas-Jaimes et al, 2021). Figura 3.…”
Section: Resultados Y Discusiónunclassified
“…Several studies have reported on the structure and microbial composition of field-collected and lab-maintained tick populations (Budachetri et al, 2014; Budachetri et al, 2017; Ross et al, 2018; Varela-Stokes et al, 2018; Thapa et al, 2019; Gill et al, 2020; Maldonado-Ruiz et al, 2021; Kumar et al, 2021; Karim et al, 2017; Zhang et al, 2019; Portillo et al, 2019; Adegoke et al, 2020; Guizzo et al, 2020; Rojas-Jaimes et al, 2021). These studies have revealed a variety of factors responsible for the differences among microbial communities between different tick samples, thus contributing extensively to our understanding of how microbial communities residing within the tick contribute to several aspects of tick biology (Ponnusamy et al, 2014; Budachetri et al, 2015; Trout-Fryxell and DeBruyn, 2016; Budachetri et al, 2018; Thapa et al, 2019; Brinkerhoff et al, 2020; Adegoke et al, 2020; Kueneman et al, 2021).…”
Section: Introductionmentioning
confidence: 99%